IMPACT OF VITAMIN E ON DIFFERENT ORGAN SYSTEMS - Koprivica, Marko; Miljković, Ana (Sanamed, 2024)
Vitamin E, present in both plant and animal-based foods, is a lipophilic compound with multifaceted biochemical functions. Its deficiency can lead to severe health consequences, while excessive intake may result in hypervitaminosis. Among tocopherols, Alpha-tocopherol stands out for its pharmacokinetic properties and potent antioxidant effects. It exerts significant influence on the immune, nervous, and cardiovascular systems, as well as on skin health. Notably, it plays a crucial role in preventing carcinogenesis. While Alpha-tocopherol garners attention, other tocopherol group members should not be overlooked, as advancements in science uncover their diverse biological impacts. In recent years, tocotrienols have emerged with distinct biochemical properties that profoundly affect human health.